A case of large left thigh liposarcoma recurrence in a 62 years old male: a case report - Kamble, Mayuri A.; Dadhich, Digvijay; Soni, Taher M.; Balwantkar, Sachin (International Surgery Journal, 2022)
We report a case of recurrence of a thigh liposarcoma in 62 years. old male, and its management. Several clinical studies of liposarcoma in extremities have been undertaken exploring the potential management and treatment of the same. Presentation of case A 62 years. old male presented with a large mass on his left thigh which was around 30×25 cm at the time of presentation, and has gradually increased since last 20 years. The patient had a similar but smaller swelling in his left thigh for which wide local excision was done earlier in the year 2000. The patient now presented with the current swelling increasing gradually since its first appearance after 5 months after the first surgery. The patient underwent CT of his left lower limb; embolization of feeder artery and debulking surgery of the mass after 10 days of the feeder embolization. Histopathology was suggestive of liposarcoma. The patient made a good recovery post procedure and was able to stand with support 8 days post-surgery.